LAYANAN BIMBINGAN KELOMPOK TENTANG TATA KRAMA PESERTA DIDIK KELAS IX SMP MUJAHIDIN PONTIANAK - Santri Tri Wansih; Muhammad Asrori; Luhur Wicaksono (Universitas Tanjungpura, 2018)
Abstract Group guidance services are a way of providing assistance (guidance) to individuals (students) through group activities. One of the most expected in the implementation of group guidance on etiquette is to improve students' behavior and prevent them from unverified acts. The research problem is